2011
DOI: 10.1007/s12094-011-0740-8
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties and CTV to PTV margins quantitative assessment using cone-beam CT technique in clinical application for prostate, and head and neck irradiation tumours

Abstract: PURPOSE To evaluate the magnitude of systematic and random errors from a subset of 100 prostate and 26 head and neck (H&N) cancer patients treated with conventional conformal radiotherapy and using image-guided radiotherapy (IGRT). After treatment, the uncertainties involved and the CTV to PTV margin were evaluated. MATERIAL AND METHODS An Elekta Synergy® linear accelerator was used, taking advantage of 3D on-board computed tomography. IGRT with no-action level (NAL) protocol was applied, reporting the 3D tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…44 Similar margins of 7.3, 7.0 and 9.0 mm in the LR, SI and AP directions were proposed for the prostate gland by quantitative assessment based on CBCT data. 45 Target dose coverage was evaluated by the proportion of the CTV encompassed by the 95% isodose for two options of 10-and 7-mm safety margins by Paluska et al 46 Kliton et al 47 suggested 9.3-, 6.5-and 8.9-mm PTV margins in the LR, SI and AP directions if in-room kV CT is used for IG. The pre-treatment CBCT images of radio-opaque markers provided information about the motion of the target immediately preceding the treatment useful for PTV margin evaluation, 48 but no correlation of these data with pre-and post-CBCT data comparison was found.…”
Section: Use Of Daily Ultrasoundmentioning
confidence: 99%
“…44 Similar margins of 7.3, 7.0 and 9.0 mm in the LR, SI and AP directions were proposed for the prostate gland by quantitative assessment based on CBCT data. 45 Target dose coverage was evaluated by the proportion of the CTV encompassed by the 95% isodose for two options of 10-and 7-mm safety margins by Paluska et al 46 Kliton et al 47 suggested 9.3-, 6.5-and 8.9-mm PTV margins in the LR, SI and AP directions if in-room kV CT is used for IG. The pre-treatment CBCT images of radio-opaque markers provided information about the motion of the target immediately preceding the treatment useful for PTV margin evaluation, 48 but no correlation of these data with pre-and post-CBCT data comparison was found.…”
Section: Use Of Daily Ultrasoundmentioning
confidence: 99%
“…Translational shifts in the prostate during the course of radiotherapy have been reported. For instance, Meijer et al (5) reported shifts of 2 to 4 mm, and Juan‐Senabre et al (6) reported shifts of 7 to 9 mm, in the position of the prostate during a radiotherapy course.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical environment, our cGAN segmentation method would detect and segment the GTV in kV images acquired during RT fractions. However, intrafraction motion during treatment would make it difficult to establish an accurate GTV location in any kV images acquired during treatment 9,10 . We view this study as a necessary but not sufficient study toward the long‐term goal of clinical implementation.…”
Section: Discussionmentioning
confidence: 95%
“…To minimize the dose delivered to healthy organs, H&N cancer patients are required to wear a skin‐tight immobilization mask that minimizes patient motion 7,8 . However, despite the restrictive nature of immobilization masks, motion in the order of several millimeters of the tumor and surrounding tissue can still occur during and between treatment fractions 9,10 . This motion can be caused by a change in the mask's fit due to patient weight loss between fractions, imperfections in the mask manufacturing and fitting process, tumor shrinkage, or treatment‐related oedema 7 .…”
Section: Introductionmentioning
confidence: 99%